2010
DOI: 10.1523/jneurosci.5673-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Polyglutamine Expression in Inducible Mouse Model Unravels Ubiquitin/Proteasome System Impairment and Permanent Recovery Attributable to Aggregate Formation

Abstract: The presence of intracellular ubiquitylated inclusions in neurodegenerative disorders and the role of the ubiquitin/proteasome system (UPS) in degrading abnormal hazardous proteins have given rise to the hypothesis that UPS-impairment underlies neurodegenerative processes. However, this remains controversial for polyglutamine disorders such as Huntington disease (HD). Whereas studies in cellular models have provided evidence in favor of UPS-impairment attributable to expression of the N-terminal fragment of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 56 publications
12
69
2
1
Order By: Relevance
“…1), similar to what has been found in other neurodegenerative diseases [167]. This is consistent with increasing evidence that Htt oligomers and not aggregates are the cytotoxic species in HD [5][6][7] and the reports of UPS inhibition before Htt inclusion into large aggregates [168][169][170]. This might explain why clinical trials of anti-aggregating molecules in HD have been so far unsuccessful [171].…”
Section: Genesis and Impact Of Er Stress In Huntington's Diseasesupporting
confidence: 87%
“…1), similar to what has been found in other neurodegenerative diseases [167]. This is consistent with increasing evidence that Htt oligomers and not aggregates are the cytotoxic species in HD [5][6][7] and the reports of UPS inhibition before Htt inclusion into large aggregates [168][169][170]. This might explain why clinical trials of anti-aggregating molecules in HD have been so far unsuccessful [171].…”
Section: Genesis and Impact Of Er Stress In Huntington's Diseasesupporting
confidence: 87%
“…A recent report demonstrated that overexpression of polyglutamine results in transient UPS inhibition in mice, but the activity returned when large inclusions formed [47]. Thus, amyloidogenic protein oligomers appear to act in a vicious manner akin to the human immunodeficiency virus, shutting down the very system expected to rid them.…”
Section: Discussionmentioning
confidence: 99%
“…Our data provide unique in vivo evidence that proteasomal insufficiency is ubiquitously encountered in various forms of inherited retinal degeneration associated with misfolding or mistargeting of both cytosolic and membrane proteins. Whereas the studies of other neurodegenerative diseases revealed a strong association between the underlying pathology and impaired proteasomal function (37)(38)(39)(40), this important stress factor largely escaped the attention of researchers studying retinitis pigmentosa and allied diseases. Given that inherited retinal disorders are typically diagnosed at their early stages, the emerging therapeutic strategies targeting proteasomes in neurodegeneration (41) could be particularly efficacious in treating these blinding conditions.…”
Section: mentioning
confidence: 99%